Culture, narrative and collective trauma - Collins, Anthony (PINS-Psychology in Society, 2015)
Alexander, Jeffrey (2012) Trauma: A social theory. Cambridge: Polity. ISBN 978-0-7456-4912-2 pbk. Pages vii + 226